2019
DOI: 10.1007/s40259-019-00387-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Immunogenicity Data in the Product Information of Biological Drugs: A Need to Report Immunogenicity Data Systematically

Abstract: Objective: To evaluate whether the current case-by-case practice leads to sufficient reporting of immunogenicity-related information in the Summary of Product Characteristics (SmPCs) of biological products approved in the European market.Methods: Immunogenicity-related information was identified and extracted from a group of 73 biological drugs that complied with drug-selection criteria. Afterwards, thirteen dichotomous questions were proposed to evaluate whether any issues are being commonly neglected.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Previous perspectives on immunogenicity in comparison with the findings in the present study Borrega et al 20 investigated the Summary of Product Characteristics of 72 biological products approved by the European Medicines Agency (EMA). They found that 81% of the products do not address the potential impact of immunogenicity on pharmacokinetics.…”
Section: Limitations Of the Present Studymentioning
confidence: 72%
See 2 more Smart Citations
“…Previous perspectives on immunogenicity in comparison with the findings in the present study Borrega et al 20 investigated the Summary of Product Characteristics of 72 biological products approved by the European Medicines Agency (EMA). They found that 81% of the products do not address the potential impact of immunogenicity on pharmacokinetics.…”
Section: Limitations Of the Present Studymentioning
confidence: 72%
“…Borrega et al 20 . investigated the Summary of Product Characteristics of 72 biological products approved by the European Medicines Agency (EMA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Running Heading: Biosimilars as an opportunity to update the Product Information of biological drugs One of the greatest theoretical clinical concerns regarding the development of biosimilars has been that post-translational protein modifications, even while antigen binding remains essentially unaltered, might result in detrimental immunogenicity. We recently demonstrated [1] that the Summary of Product Characteristics (SmPCs) of biological drugs, approved by the European Medicines Agency (EMA), are very heterogeneous regarding the issues related to immunogenicity that are addressed within these documents.A complementary analysis, using the methodology advanced in [1], to the EMA's documents "Procedural steps taken and scientific information after the authorisation" shows that 57% (30/69) of the biological drugs that have been authorized prior to 2012 did not update their SmPC at least once when it comes to information related to unwanted immunogenicity. These are surprising results given the advancements that have been seen in the field of immunogenicity assessment [2], namely in the development of more
…”
mentioning
confidence: 99%
“…A complementary analysis, using the methodology advanced in [1], to the EMA's documents "Procedural steps taken and scientific information after the authorisation" shows that 57% (30/69) of the biological drugs that have been authorized prior to 2012 did not update their SmPC at least once when it comes to information related to unwanted immunogenicity. These are surprising results given the advancements that have been seen in the field of immunogenicity assessment [2], namely in the development of more…”
mentioning
confidence: 99%